Cyanobacteria: Photoautotrophic Microbial Factories for the Sustainable Synthesis of Industrial Products. (25th June 2015) - Lau, Nyok-Sean; Matsui, Minami; Abdullah, Amirul Al-Ashraf
Abstract : Cyanobacteria are widely distributed Gram-negative bacteria with a long evolutionary history and the only prokaryotes that perform plant-like oxygenic photosynthesis. Cyanobacteria possess several advantages as hosts for biotechnological applications, including simple growth requirements, ease of genetic manipulation, and attractive platforms for carbon neutral production process. The use of photosynthetic cyanobacteria to directly convert carbon dioxide to biofuels is an emerging area of interest. Equipped with the ability to degrade environmental pollutants and remove heavy metals, cyanobacteria are promising tools for bioremediation and wastewater treatment. Cyanobacteria are characterized by the ability to produce a spectrum of bioactive compounds with antibacterial, antifungal, antiviral, and antialgal properties that are of pharmaceutical and agricultural significance. Several strains of cyanobacteria are also sources of high-value chemicals, for example, pigments, vitamins, and enzymes. Recent advances in biotechnological approaches have facilitated researches directed towards maximizing the production of desired products in cyanobacteria and realizing the potential of these bacteria for various industrial applications. In this review, the potential of cyanobacteria as sources of energy, bioactive compounds, high-value chemicals, and tools for aquatic bioremediation and recent progress in engineering cyanobacteria for these bioindustrial applications are discussed.